FAKTOR RISIKO ANEMIA PADA SANTRI PUTRI DI PONDOK PESANTREN DARUSALAM BOGOR Risk Factor of Anemia among Female Students in Darusalam Islamic Boarding School Bogor - Ikeu Ekayanti; Rimbawan Rimbawan; Dewi Kusumawati (Media Gizi Indonesia, 2020)
Adolescent girls are vulnerable group to anemia. Students who live in dormitories tend to have less intake that can cause iron defi ciency. This study aimed to determine the risk factors of anemia among female students in the Darusalam Islamic Boarding School Bogor. This was an observational study with a cross sectional design. Subjects were 84 female students who selected purposively by inclusion and exclusion criteria. Anemic status was determined by measuring hemoglobin levels with HemoCue 301. Data on subjects characteristics, health status, menstrual status, skipping meal behavior collected by questionnaire. Level knowledge, attitudes and nutrition practices related to anemia assessed by of fi ve questions for each indicators. Nutritional status is assessed based on BMI/A indicator. The intake data was obtained by the 2×24 hour food record method collected by questionnaires. Statistical analysis using chi-square test and logistic regression. Students with mild anemia were 38.1%, while 20.2% had moderate anemia. Intake of energy, protein, iron, vitamin C were inadequate. The results of bivariate analysis showed that skipping meals were signifi cantly associated with anemia status (p=0.007; OR 4.0; 95% CI 1.4-11.4). Nutritional attitudes also had a signifi cant relationship with anemia status (p=0.048; OR 2.6; 95% CI 1.0-6.6). The results of the logistic regression test showed that the variables associated with anemia were skipping meals (p=0.024; OR 3.5; 95% CI 1.0-11.8). Islamic boarding schools are expected to provide balanced healthy and nutritious food and provide nutrition education so it can support the improvement of student’s health status.